Comparison of the effects of spinal anesthesia, paracervical block and general anesthesia on pain, nausea and vomiting, and analgesic requirements in diagnostic hysteroscopy: A non-randomized clinical trial - Manouchehrian, Nahid; Pilehvari, Shamim; Rahimi-Bashar, Farshid; Esna-Ashari, Farzaneh; Mohammadi, Shaghayegh (Frontiers in Medicine, 2023)
Background The aim of this study was to compare the effect of spinal anesthesia (SPA), paracervical block (PB), and general anesthesia (GA), on pain, the frequency of nausea and vomiting and analgesic requirements in diagnostic hysteroscopy. Methods This single-center, non-randomized, parallel-group, clinical trial was conducted on 66 diagnostic hysteroscopy candidates who were selected by convenience sampling at Fatemieh Hospital, in Hamadan, Iran, in 2021. Results The mean pain score during recovery and the need for analgesic injections was found to be significantly higher in the GA group compared to that in the SPA group (pain: 3.77 ± 2.25 vs. 0.10 ± 0.30, P < 0.001), (analgesic: 50 vs. 0%, P < 0.001) and PB group (pain: 3.77 ± 2.25 vs. 0.90 ± 1.37, P < 0.001), (analgesic 50 vs. 10%, P < 0.001), respectively. However, no statistically significant difference was observed between the mean pain score between SPA and PB groups (0.10 ± 0.30 vs. 0.90 ± 1.3, P = 0.661). In addition, there were no significant differences between groups on nausea/vomiting after operation (P = 0.382). In adjusted regression analysis (adjusting for age, weight, gravid, abortion, and cause of hysteroscopy), the odds ratio (OR) of pain score during recovery was increased in PB (OR: 4.471, 95% CI: 1.527–6.156, P = 0.018) and GA (OR: 8.406, 95% CI: 2.421–9.195, P = 0.001) groups compared with the SPA group. However, in adjusting based on times of surgery duration, anesthesia duration, recovery and return of motor function, the ORs of pain score between groups was not statistically significant. Conclusion Despite reduced pain during recovery in patients receiving SPA, duration of anesthesia, recovery period, and return of motor function were significantly prolonged compared to those receiving PB or GA. It seems that PB with less recovery time and faster return of motor function than SPA and also mild pain during recovery compared to GA can be a good option for hysteroscopy. Clinical trial registration http://www.irct.ir, identifier IRCT20120915010841N26.